Produtividade e eficiência do uso do nitrogênio na cultura do milho inoculado com Azospirillum brasiliense - Viana, Marcelo Marinho (2017)
The Association of nitrogen with diazotrophic bacteria of the Azospirilum brasilense genus can ensure greater productive capacity and nitrogen use efficiency to the culture of corn. In order to test this hypothesis was evaluated the association between Azospirillum brasilense forms inoculation and rate of N on the grain productivity and nitrogen use efficiency by corn cultivation. Two experiments were carried out in the field (2015 and 2016), in a randomized complete block design, with four replications. The treatments were performed in factorial arrangement 4 x 3: four N fertilization rates (0, 45, 90 and 180 kg ha-1 ), applied as top-dressing with three inoculation way (seeds, leaf and control). Urea (45% of N) was N source. Nitro 1000 Gramíneas® was the inoculant used in the treatments. It was performed with 100 mL ha-1 of the commercial product in seedinoculant before planting and 200 mL ha-1 in leaf-inoculant spraying application. The N fertilization rates and A. brasilense leaf-inoculant spray were applied at the corn growth stage V4. The variable evaluated were: grain yield (GY, Mg ha-1 ), N harvest index (NHI), harvest index (HI), N remobilization (NR, kg ha-1 ), N remobilization efficiency (NRE, %), N utilization efficiency (NUtE, kg kg-1 ), N uptake efficiency (NUpE, kg kg-1 ) and agronomic efficiency (AE, kg kg-1 ). With these results we can conclude that there was increase of 50 and 20% in GY and 50 and 42% in NUE in seed-inoculant treatment when compared with control, in 2015 and 2016, respectively. N fertilization rates affect positively the GY and reduce NUE and its components.